The importance and meaning of sagas in the ideas of the Estonian Germanist Rein Sepp - Kulmar, Tarmo (Universität Tübingen, 2004)
Rein Sepp, the great Germanist of the 20th century Estonia, was born on April 23, 1921. His studies at the University of Tartu were interrupted by World War II, in which he participated in the ranks of the Nazi German army. After a Soviet prison camp in Siberia he committed himself to translating various writings, mainly from the Old Icelandic, German and English languages: Saemundra-Edda (1970), Nibelungenlied (1977), Parzival (1989), Beowulf (1990), Snorra-Edda (1990), Anglo-Saxon Chronicles and Early English Poems (1992). As a member of the students’ corps “Sakala”, he mentored several generations of students, who often visited him in his country home. Rein Sepp died on January 25, 1995. Rein Sepp’s personality was strongly influenced in its formative stages by the atmosphere in his home (one of his uncles was Hendrik Sepp, an Estonian historian), his travel years and tough experiences, his good knowledge of human nature, his outstanding linguistic talent and, naturally, his extensive knowledge both of medieval history and culture and of natural and exact sciences. He was characterized by original thinking and the capability of generating extraordinary ideas. Modest in recording his ideas on paper, he was all the keener to present and argue for them in private conversations. *Following is an analysis of Rein Sepp’s ideas about the origins and meaning of Saemundra-Edda. For Rein Sepp, the central issue was man’s identity, and the main concern was loss of that identity everywhere within the reach of modern European culture. He deemed such degeneration to have been caused by increasing superficiality, recklessness and irresponsibility. “The ice age draws on when people working the land grow tired for some reason, resulting in the neglected nature slacking off and cooling down in its turn,” wrote R. Sepp, and continued, “Since the deathly silence of the ice age is caused by people’s tiredness, thoughtlessness or slackness, we need to maintain alertness and ability to perform in order to avoid spiritual dying out in the first place, and to strive for the integrity of man and nature.” To this end, a text interpreting for man the world as well as man’s place and purpose in it might, in R. Sepp’s opinion, serve as the order-generating foundation. For him, such a text was first and foremost Saemundra-Edda - “a text that is mentally alive and dynamic” - which raises questions at a very high level and contains millennia of experience. R. Sepp was of the opinion that during the post-ice age millennia, there emerged in Scandinavia and the Eastern Baltic region a way of life that he called “ancient Nordic culture”. He identified it with the archeologically established proto-European Kunda culture in the Eastern Baltic region, which apparently had a strong impact on the neighbouring lands and ethnic groups. He considered its centre to be the surroundings of Lake Võrtsjärv in Estonia. He deemed the lake’s name, Võrtsjärv, to contain the genitive of Vyrd (Urdr), an Old Scandinavian name for God. In the subsequent millennia, which saw the immigration to the Baltic region of proto-Indo-European tribes, the ancient Nordic people were assimilated into and passed on to the former their worldview and experience. The ideology of the ancient Nordic people led to the separation of the Estonian and Livonian peoples from the rest of the Balto-Finnic peoples as well as that of North Germanic peoples and proto-Baltic peoples from the rest of the Indo-European peoples. This would mean that many of the words in the Estonian language that are considered to be loans from the Old Germanic language are actually Ancient Nordic loans to both Old Germanic and the Balto-Finnic languages. Rein Sepp was convinced that Saemundra-Edda was not an original North Germanic work but a phenomenon of the ancient Nordic culture, which later germanised. In Saemundra-Edda there is undoubtedly a very strong stratum of the Indo-European North Germanic culture; however, it is a much later one than the ancient Nordic stratum. For instance, he thought that among the 18 most important Old Scandinavian deities, 16 were of ancient Nordic origin. Further, the text and the development of Saemundra-Edda show in their turn that the substratum of the ancient Nordic culture survived the longest in Iceland, one of the latest regions in Europe to be influenced by Christianity, where the influence was also one of the weakest. Thus, the ancient Nordic culture did not disappear but was preserved as a somewhat concealed foundation of the Old Scandinavian culture endowing the latter with creativity and order. Rein Sepp supposed that on Estonian territory the traces of the ancient Nordic culture could most often be observed in West and South West Estonia: in the use of numerals, in the toponymy and in the behavioural logic. The traces manifest themselves in the conduct and mutual communication of people, the placement of buildings and roads in nature and in the place names and their logical relationship to the landscape and other names. Many Estonian and Latvian place names, which mean nothing in their respective languages, do have a meaning in Old Icelandic (as, for instance, Võrtsjärv, Ipiki, Igali and Vingali). Even today, the placement of buildings on the landscape would often betray a high degree of resemblance to that described in some passage of Saemundra-Edda, and one may come across the psychological and physical types of humans described in the Eddas and see them behave according to the same logic as recorded in the ancient sagas. Thus, Rein Sepp deemed that the oldest strata of the beginnings and development of Saemundra-Edda may originate from the Mesolithic proto-European Kunda culture in the Eastern Baltic region, one of the common sources for the Balto-Finnic, the Baltic and the Old German (particularly, of course, Old Scandinavian) culture, way of life and thinking. This standpoint was unexpectedly supported by the recent studies of the Finnish linguist Kalevi Wiik, which imply that the traces of the substrate tribes in the languages and cultures of the Nordic peoples are much better observable than those of the Finno-Ugrian tribes, which later immigrated from the east. That substratum in the Eastern Baltic region as well as, to a great extent, in Scandinavia, is exactly the proto-European Kunda culture, along with its archaeologically established neighbouring cultures. This would mean that the deepest roots of Saemundra-Edda, which was set down in Iceland in the 11th and 12th centuries, reach back in time for at least seven thousand years, to the ancient Nordic era, which was the oldest common prehistoric period for the entire Nordic region. “We do not know what was accomplished or initiated in these spiritual, natural and historical developments and beginnings here on these strips of land to the east of the Baltic sea, for instance. We can only guess that the further back into the past, the more united must have been the ancient Nordic prose of existence. As the nature grew more varied, however, it became more diversified, and increasingly so with the passage of time.”